1993
DOI: 10.1007/bf00019954
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of putative defense-related genes from Arabidopsis thaliana and expression in fungal elicitor-treated cells

Abstract: Numerous Arabidopsis genes have been cloned that correspond to putative pathogen defense-related genes identified in parsley (Petroselinum crispum). Treatment of Arabidopsis cells with fungal elicitor leads to rapid accumulation of the respective mRNAs with time courses comparable to those observed for their counterparts in parsley. Evolutionary sequence conservation of many of these genes in several plant species suggests they code for important plant functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
81
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 20 publications
(19 reference statements)
3
81
0
1
Order By: Relevance
“…The Arabidopsis (Arabidopsis thaliana) cell line At7 was described previously (Trezzini et al, 1993;Hartmann et al, 1998). Seedlings for quantitative real time RT-PCR, HPLC analysis, and photometric anthocyanin analysis were grown in petri dishes on Whatman-paper soaked with Murashige and Skoog medium lacking Suc under sterile conditions.…”
Section: Cell Culture and Plant Materialsmentioning
confidence: 99%
“…The Arabidopsis (Arabidopsis thaliana) cell line At7 was described previously (Trezzini et al, 1993;Hartmann et al, 1998). Seedlings for quantitative real time RT-PCR, HPLC analysis, and photometric anthocyanin analysis were grown in petri dishes on Whatman-paper soaked with Murashige and Skoog medium lacking Suc under sterile conditions.…”
Section: Cell Culture and Plant Materialsmentioning
confidence: 99%
“…Plant material was harvested, frozen in liquid nitrogen and stored at )80°C until use. The A. thaliana cell line At7 which grows in the dark has been described previously (Trezzini et al, 1993;Hartmann et al, 1998). To block de novo protein synthesis, protoplasts derived from At7 cells were treated with 10 lM cycloheximide; the drug was added to the culture 30 min before the onset of light irradiation.…”
Section: Cell Culture and Plant Materialsmentioning
confidence: 99%
“…The presence of this gene in other plant species, such as potato (Solanum tuberosum), alfalfa (Medicago sativa), and Arabidopsis thaliana (At) was also demonstrated (6). Subsequently, two sequence-related counterparts of eli3 in parsley were isolated from A. thaliana (Ateli3-1 and Ateli3-2), and their expression was shown to be induced by fungal elicitor in cultured A. thaliana cells (6). Additional evidence for an important role of the eli3 gene product in plant disease resistance came from genetic studies demonstrating that eli3 expression was dependent on the presence of the RPMI resistance gene in A. thaliana (7).…”
mentioning
confidence: 94%
“…Expression of this gene was shown to be rapidly and transiently stimulated in cultured parsley cells upon treatment with a cell wall preparation (elicitor) from the phytopathogenic fungus Phytophthora sojae, and histochemical studies revealed local and rapid accumulation of ELI3 mRNA around fungal infection sites in parsley leaves (5). The presence of this gene in other plant species, such as potato (Solanum tuberosum), alfalfa (Medicago sativa), and Arabidopsis thaliana (At) was also demonstrated (6). Subsequently, two sequence-related counterparts of eli3 in parsley were isolated from A. thaliana (Ateli3-1 and Ateli3-2), and their expression was shown to be induced by fungal elicitor in cultured A. thaliana cells (6).…”
mentioning
confidence: 95%